Conformationally Restricted Aza‐Dipyrromethene Boron Difluorides (Aza‐BODIPYs) with High Fluorescent Quantum Yields. Issue 3 (21st January 2014) - Jiao, Lijuan; Wu, Yayang; Ding, Yin; Wang, Sufan; Zhang, Ping; Yu, Changjiang; Wei, Yun; Mu, Xiaolong; Hao, Erhong
Abstract A simple approach to the highly fluorescent near‐infrared aza‐BODIPY dyes with higher fluorescence quantum yields (up to 0.81 in toluene) in comparison with their known analogues is presented. Our approach is based on the restricted rotations of the 1, 7‐phenyl groups to the mean plane of the aza‐BODIPYs, which is achieved through the installation of bulky substituents on the 1, 7‐phenyl groups of aza‐BODIPYs and results in a reduced nonradiative relaxation process in solution. The large torsion angles between the 1, 7‐phenyl groups and the aza‐BODIPY core (ϕ1 and ϕ2 in these novel conformationally restricted aza‐BODIPYs) were confirmed by X‐ray diffraction studies.